A General Self‐Assembly Induced Strategy for Synthesizing 2D Ultrathin Cobalt‐Based Compounds Toward Optimizing Hydrogen Evolution Catalysis. (25th October 2022) - Guo, Xingmei; Duan, Mengting; Zhang, Junhao; Xi, Baojuan; Li, Ming; Yin, Rui; Zheng, Xiangjun; Liu, Yuanjun; Cao, Fu; An, Xuguang; Xiong, Shenglin
Abstract: Exploring a general method for synthesizing 2D compounds with high accessible surface area and nano‐thickness as advanced electrocatalysts is essential yet challenging. Herein, a self‐assembly induced reverse micelle templating method followed by topochemical transformation is developed to synthesize a series of cobalt‐based compounds with varied anions and similar ultrathin 2D structures. Electrocatalytic behaviors for the hydrogen evolution reaction (HER) are systematically investigated, which demonstrate enhanced performances of ultrathin 2D compounds than their agglomerated counterparts. Among them, 2D CoP is particularly prominent. The overpotential of 144 mV at 10 mA cm −2, together with superb stability, place it among the best single‐phase phosphide HER catalysts reported thus far. Theoretical calculation and experimental results demonstrate the favorable valence electronic structure with moderate hydrogen adsorbability and good intracrystalline conductivity, as well as the homogeneous ultrathin 2D configuration with sufficiently exposed active sites and shortened intracrystalline electron transport route, are the dominant reasons that 2D CoP exhibits optimal electrocatalytic activity for HER. This study presents a novel and extendable strategy for synthesizing various 2D metal‐based compounds with valuable insights into the modulation essence of advanced electrocatalysts. Abstract : A general self‐assembly induced reverse micelle templating‐topochemical transformation strategy is developed to synthesize cobalt‐based compounds with different anions and similar ultrathin 2D structures, which breaks the layered‐crystal limitation of the conventional exfoliation method. Optimal electrocatalytic behavior for hydrogen evolution reaction is demonstrated on 2D CoP, which derives from the favorable valence electronic structure and homogeneous ultrathin configuration.